Mechanics of Microstructured Solids 2 Cellular Materials, Fibre Reinforced Solids and Soft Tissues - Ganghoffer, Jean-Franȯis.; Pastrone, Franco. (Lecture Notes in Applied and Computational Mechanics,, 2010)
This second volume of the series Lecture Notes in Applied and Computational Mechanics is the second part of the compendium of reviewed articles presented at the 11th EUROMECH-MECAMAT conference entitled "Mechanics of microstructured solids: cellular materials, fibre reinforced solids and soft tissues", which took place in Torino (Italy) in March 10-14, 2008, at the Museo Regional delle Scienze. This EUROMECH-MECAMAT conference was jointly organized by the Dipartimento di Matematica dell'Universit ̉di Torino, Italy and the INPL Institute (LEMTA, Nancy-Universit,̌ France). Prof. Franco Pastrone and Prof. Jean-Franȯis Ganghoffer were the co-chairmen.